A Past Which Refuses to Become History:: Nazism, Niagara Falls, and a New National Identity in Suzette Mayr’s The Widows - Wolf, Doris (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2002)
Through the experiences of Hannelore Schmitt, a German war widow, Suzette Mayr locates The Widows in the context of debates in contemporary German society about Nazi brutality. The novel suggests that it is only through a confrontation with history that German citizens can experience liberation, not only at the level of the individual citizen, but also at the national policy level. Simultaneously, the novel expresses skepticism about the Canadian immigrant identity, parodying historians who have constructed Canada's cultural memory in the contemporary multicultural movement. The creation of a utopian women's community at the novel's end therefore suggests the vision of a nation which truly incorporates difference into its daily life.